2010
DOI: 10.1155/2010/358372
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence and Photochemical Investigations of Phytochrome in Higher Plants

Abstract: In higher plants, photoreceptor phytochrome (phy)—photoisomerizing biliprotein working as a light-driven molecular switch—is represented by a small family of phytochrome gene products with phyA and phyB as major species. phyA is unique among other phytochromes mediating photoresponse modes specific only for this pigment (far-red light induced) and also photoresponses characteristic of phyB and other minor phys (red light induced). In our group, in vivo fluorescence investigations of phytochrome were initiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…For this, we used etiolated maize seedlings and followed variations in the spectroscopic and photochemical parameters of phyA, which depend on plant organ/tissues and on the stage of its development. In agreement with our earlier findings of the phyA heterogeneity , we can interpret them as a manifestation of the presence of the two phyA species in the cell—the longer wavelength, at low temperatures photochemically active species phyA′ and the shorter wavelength at low temperatures photochemically inactive phyA′′. Evaluations of their content in tissues (this work and ) have shown that it changes in the growing etiolated plant, even tissue specific, as observed by the phyA′/phyA′′ content in a developing maize root.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…For this, we used etiolated maize seedlings and followed variations in the spectroscopic and photochemical parameters of phyA, which depend on plant organ/tissues and on the stage of its development. In agreement with our earlier findings of the phyA heterogeneity , we can interpret them as a manifestation of the presence of the two phyA species in the cell—the longer wavelength, at low temperatures photochemically active species phyA′ and the shorter wavelength at low temperatures photochemically inactive phyA′′. Evaluations of their content in tissues (this work and ) have shown that it changes in the growing etiolated plant, even tissue specific, as observed by the phyA′/phyA′′ content in a developing maize root.…”
Section: Discussionsupporting
confidence: 92%
“…Low‐temperature emission spectra (λ ex = 633 nm, normalized at the maximum) of phytochrome A in the maize root tip (Kubanskaya var.) at the initial stage 1 of its development: emerging root ( L = 0.7 mm), root at the end of stage 1 ( L = 2 mm).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations